2014
DOI: 10.1007/s00453-014-9896-2
|View full text |Cite
|
Sign up to set email alerts
|

The (Weighted) Metric Dimension of Graphs: Hard and Easy Cases

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 16 publications
0
78
0
Order By: Relevance
“…We refer to e.g. [1,12,16,17,18,19,21,29,31] for some results. On the positive side, Identifying Code, Locating-Dominating-Set and Open Locating-Dominating Set are linear-time solvable for graphs of bounded clique-width (using Courcelle's theorem [15] ).…”
Section: Similarly a Graph Admits An Open Locating-dominating Set Ifmentioning
confidence: 99%
“…We refer to e.g. [1,12,16,17,18,19,21,29,31] for some results. On the positive side, Identifying Code, Locating-Dominating-Set and Open Locating-Dominating Set are linear-time solvable for graphs of bounded clique-width (using Courcelle's theorem [15] ).…”
Section: Similarly a Graph Admits An Open Locating-dominating Set Ifmentioning
confidence: 99%
“…In this work, Diaz et al also showed that this problem is solvable in polynomial time on the class of outer-planar graphs. Subsequently, Epstein et al [7] showed that this problem is NPcomplete on split graphs, bipartite and co-bipartite graphs. Subsequently, Epstein et al [7] showed that this problem is NPcomplete on split graphs, bipartite and co-bipartite graphs.…”
Section: Metric Dimensionmentioning
confidence: 99%
“…As further recent work related to this paper, we remark that the metric dimension of t-trees has recently been investigated in [5], and the treelength of a graph has recently been used to design algorithms to compute the metric dimension [6]. Algorithms and complexity results regarding the computation of the metric dimension of graphs belonging to graph classes considered in the present paper, can be found in [14,16,18].…”
Section: Introductionmentioning
confidence: 89%